Barriers to healthcare delivery in Iranian prisons: a qualitative study. Issue 4 (17th August 2020) - Hajebrahimi, Ahmad; Alimohammadzadeh, Khalil; Hosseini, Seyed Mojtaba; Maher, Ali; Bahadori, Mohammadkarim
Abstract : Purpose: High quality health-care delivery is not only the governments' responsibility but also every prisoner's right. Health care in prison and, particularly, of Iranian prisoners is increasingly important topic because of the rising number of the prison population. This paper aims to explore health-care managers' perspectives and experiences of prisons and the barriers to health-care delivery in Iranian prisons. Design/methodology/approach: A qualitative research design was conducted in Iran from October 2018 to August 2019. The participants consisted of 51 health-care managers (50 men and one woman) from Iranian prisons. A combination of face-to-face (N = 42) and telephonic (N = 9) semi-structured interviews were used because of the geographical distribution of the respondents. The first part of the interview guide consisted of demographic characteristics, and the second part consisted of three main open ended-questions. Interviews were recorded and transcribed, and thematic descriptive analysis was used to interpret the data. Findings: The barriers to health-care delivery in Iranian prisons were categorized into four main topics: human resources, financing, facilities and barriers related to the health-care delivery process. Data synthesis identified the following themes for barriers to human resources: barriers to human resources planning (with eight sub-themes); barriers to education (with three sub-themes); and motivational barriers (with seven sub-themes). Moreover, barriers to financing consisted of five sub-themes. The barriers to facilities consisted of barriers related to physical infrastructures (with two sub-themes) and barriers related to equipment (with six sub-themes). Finally, barriers to the health-care delivery process included the following themes: communication barriers (with six sub-themes); legal barriers (with five sub-themes); and environmental-demographic factors (with seven sub-themes). Originality/value: Identifying the barriers to health-care delivery in Iranian prisons plays a critical role in the improvement of planning, decision-making and the health-care delivery process.